SINGAPORE: A CITY, A STORY, A BRAND - Varshini S (International Journal of Engineering Technologies and Management Research, 2025)
Singapore or the little red dot, a small city-state which has positioned itself in such a way that everyone imagines it to be a land of technological innovation, this proves that a country can also be a brand. Building a new identity is the ultimate goal for branding which helps any business or a product to be accepted or sold faster than others this concept can also be applied nations with the concept of “Nation branding”. This nation branding is important for every country just like how important it is in the corporate world. Nation branding is relatively a new concept coined by Simon Anholt in 1996, it suggests that the reputation of a country behaves, rather like the brand images of companies and products. As such, a nation’s brand can have a significant bearing on its prosperity, welfare, and effective administration. (Murphy, 2022). There is a common conception that a nation projects itself to be a better brand than others to promote tourism but its often more than just tourism sometimes a country would want to gain political and economic attention or to attract Foreign Direct Investment (FDI) or to erase past misconceptions or when a country is transitioning from an age old political or economic stance or to showcase its uniqueness from others. But moreover nation branding increases the Competitive Advantage of a nation, encompassing many sectors, including attracting tourists, investors, entrepreneurs, and foreign consumers of a country’s products and services. (Dinnie, 2008).